“ЎТИН ТЎЙИ” УДУМИНИНГ ЛОКАЛ ХУСУСИЯТЛАРИ - Худайқулова, Л. (SCIENCE and SOCIETY, 2022)
This article discusses the antiquity and historical basis of such rites as “collection of firewood” or “wedding of firewood” and “non pishirar”, which are part of the circumcision wedding ritual, celebrated among the population living in the territory of Southern Uzbekistan.
Keywords: folklore; wedding; tradition; rite; system; sumbol; imagination; spirit; mythology